Molecular mechanisms of neuronal death in brain injury after subarachnoid hemorrhage - Chen, Junhui; Li, Mingchang; Liu, Zhuanghua; Wang, Yuhai; Xiong, Kun (Frontiers in Cellular Neuroscience, 2022)
Subarachnoid hemorrhage (SAH) is a very common cerebrovascular disease with high disability and death worldwide. The pathophysiological process and mechanisms involved in aneurysm rupture in SAH are quite complex and divided into early brain injury (EBI) and delayed brain injury (DBI). The initial mechanical insult results in brain tissue and vascular disruption with hemorrhages and neuronal necrosis, and subsequently, secondary injury is evoked, resulting in diffuse cerebral damage in the peri-core area. The molecular mechanisms of neuronal death following aneurysmal subarachnoid hemorrhage are complex and are not entirely understood. Regarding the pathogenesis of brain damage, multiple cell death pathways were stimulated. Particular attention should be devoted to necrosis, apoptosis, autophagy, necroptosis, pyroptosis, and ferroptosis. In the present review, we discuss the mechanism of neuronal death after SAH and its influence on brain injury after SAH.